A cross‐sectional analysis of the demand for coffee in the United States. Issue 2 (18th November 2022) - Capps, Oral; Cheng, Muxi; Kee, Jennifer; Priestley, Samuel L.
Abstract: The purposes of this study were to develop a profile of households who purchase coffee, to determine the socioeconomic determinants of the demand for coffee by US households, and to update the own‐price, cross‐price, and income elasticities of demand for US households. The profile suggests to targeting wealthier households, households without children living in the household, older households, white households, and households located in the Pacific region and in New England. The own‐price elasticity of −1.93 indicates that the demand for at‐home purchases of coffee is elastic. Tea is a substitute for coffee. Given the income elasticity of 0.20, changes in household income are not likely to have sizeable impacts on at‐home coffee consumption. Nevertheless, coffee is a necessity in economic parlance. The source of data for this analysis was the NielsenIQ pertaining to 61, 380 households for calendar year 2015. [EconLit Citations: D1, D9, D12].